Methodology for Internal Damage Percentage Assessment by Subterranean Termites in Urban Trees - Francisco José Zorzenon; Ana Eugênia de Carvalho Campos (Sociobiology, 2014)
One of the most important problems in urban trees is termite infestation. Simple observations of damages on outside trunks or dead branches and leaves do not always confirm infestations. Several trees may present severe termite damage internally that can only be observed through drilling. This paper presents a methodology to evaluate estimated percentages of internal damage caused by termites in urban trees. Tests were made on 1,477 plants in a neighborhood in the city of São Paulo, Brazil and 27% of them were infested by subterranean termites. The results showed that the methodology is simple to use, fast and inexpensive, and it allows assessment of termite internal damage which may help in making decisions on tree management. The trees did not show any phytosanitary problems along the 9 year study after being submitted to the new technique.